If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4t + 7 + -1t = 18 Reorder the terms: 7 + 4t + -1t = 18 Combine like terms: 4t + -1t = 3t 7 + 3t = 18 Solving 7 + 3t = 18 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 3t = 18 + -7 Combine like terms: 7 + -7 = 0 0 + 3t = 18 + -7 3t = 18 + -7 Combine like terms: 18 + -7 = 11 3t = 11 Divide each side by '3'. t = 3.666666667 Simplifying t = 3.666666667
| 2y+7=2y+7 | | .75w-.5w-4=12 | | 11b-9b+5=17 | | y^2+2xy+2x-5=0 | | g=ar | | 1.75w-.5w-4=12 | | -2-3x=3+ | | -7y+6=-8y+4 | | 2x+3y-20=-15 | | -56+42x=6x+6 | | 8[5x+7(3+4x)]-16x-8= | | 3-5q=9-4q | | 0.01x-0.1=-x+10 | | 3x+5x+20= | | 5d+2(2d-3)-(-2)= | | 63x^2+72x^2= | | 4(2x-6)=18 | | p+1=-49 | | 12=-n+8 | | 1200+9x=25x | | -2+8y=12 | | -2x+10=-44 | | 8m-(-3)+5(m+3)= | | -9b+27=72 | | 3x+8+2x-5=23 | | 22=(b+3) | | x^2-3x-y=0 | | -2(b-9)=2 | | 12x+3=6x-15 | | 7x^2-y^2=31 | | 20x^4-12x^2=0 | | (x-6)(x-4)=-1 |